Open-lock house door using digital lock code / Mohamad Firdaus Mohd Zabri, Muhammad Faris Din and Muahamd Rizuan Ramlan - Mohd Zabri, Mohamad Firdaus; Din, Muhammad Faris; Ramlan, Muhamad Rizuan (2013)
The aim of this project is to develop a reliable house lock door by using digital lock code. This system can be used especially to main house door or secret door. The main purpose of this project is to keep our house in a safe condition. By using this system, thieves or burglars cannot easily disable or opened the door. People also cannot make a duplicate copy to the key because it using a code system.